Exploring Valuable Lipids in Diatoms - Yi, Zhiqian; Xu, Maonian; Di, Xiaxia; Brynjolfsson, Sigurdur; Fu, Weiqi (Frontiers in Marine Science, 2017)
Diatoms are one major group of algae in oceans that accounts almost half of marine primary food production and have also been identified as a promising candidate for biofuel production for their high level accumulation of lipids. They have gained increasingly attention for their potential applications in pharmaceuticals, cosmetics, nutrient supplements and biofuels. This review aims to summarize the recent advances in diatom lipid study. Chemical structures and bioactivities of different lipid classes are discussed with a focus on valuable lipids such as fatty acids, polar lipids, steroids, and oxylipins from various diatoms species. Further, current extraction and fractionation approaches are compared and recent analytical techniques and methods are also reviewed with an emphasis on lipid class composition and fatty acid profiling. Biosynthetic pathways and key catalyzing enzymes are illustrated for a better understanding of fatty acid metabolism. Past engineering attempts towards generating appropriate diatom strains for lipid production are discussed with examples using mutagenesis, environmental stimulants and genetic modification methods. Some possible future directions and applications of diatom-derived lipids are also proposed.